Investigation of anti-arthritic potential of Acacia torta (roxb.) craib - N., Girish; K. V., Anil Kumar; Nagaraju, Beere (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Acacia torta (Roxb.) Craib, traditionally used in respiratory, circulatory, digestive, musculo-skeletal, skin diseases etc., Numerous plants of this genus have been used in folk medicine to treat stomach pain, cough, diarrhoea, piles, sore-throat; as astringent, antipyretic, antimicrobial, antimalarial, antiviral, anti-oxidant and as anti-hypertensive. Hence, the present study was aimed to investigate the anti‐arthritic potential of Acacia Torta (Roxb.) Craib, since, systematic study of this plant has not been carried out. Methods: Ethanol and water were used to prepare stem extract by soxhlet extraction method. The extract is evaluated by using Freund’s complete adjuvant induced arthritis in albino wistar rats at the dose of 100mg/kg/p.o. and 400mg/kg/p.o. and indomethacin at 10mg/kg were used for the study. Results: The hydro alcoholic extract of the stem Acacia torta (Roxb.) Craib in crude form contains phytoconstituents like saponins, tannins, steroids, and triterpenes. The reference standard, Indomethacin at the dose of 10 mg/kg showed significant inhibition of paw edema by 71.61% (P <0.001), as compared to the vehicle control. Treatment with the hydro alcoholic extract of stem Acacia Torta at doses of 100 and 400 mg/kg caused significant inhibition of paw edema by 59.26% (P <0.001) and 69.14% (P <0.001) respectively, was observed on 21st day, as compared to the vehicle control. Conclusions: The data obtained from the present study indicated that several factors may contribute to the anti-inflammatory and anti-arthritic activity of hydro alcohol extract of the stem Acacia torta (Roxb.) Craib. adjuvant induced arthritis showed inhibition of prostaglandin synthesis might be the major mechanism by which the hydro alcoholic extract of the stem Acacia torta (Roxb.) Craib exerts anti-inflammatory and arthritic activity.